EPIDEMIOLOGY OF PRIMARY HYPERPARATHYROIDISM – INVISIBLE PART OF THE ICEBERG (LITERATURE REWIEW) - I. A. Baranova; T. V. Klemushina; T. A. Zykova (Медицинский вестник Юга России, 2016)
An overview of Russian and foreign literature data with an analysis of the epidemiology of primary hyperparathyroidism (PGPT) was made. It wasnoted, that previously PHPTwas considered a severe disabling disease with the development of complications such as nephrolithiasis and osteoporosis. However,recently, the data of population-screening studies of blood calcium in several countries in Europe and North America opened the «invisible part of the iceberg» - a large number of mild (olygosymptomatic and asymptomatic) forms of the disease.According to different authors, the prevalence of PHPT is 0.5 to 34 cases per 1000 population, i.e.about 1%, and among people over 55 years – about 2%. NormocalciemicPHPT – a newly detected form nowadays is of particular interest. To date, analysis of blood calcium in Russia is not a routine biochemical test, and patients with PHPToften receive specialized care at the stage of irreversible complications. Therefore, it is necessary to increasethe awareness of physicians about the epidemiology and clinical presentation of the disease, to identify risk groups of PHPTand implement the diagnostic algorithms in the daily doctor’s practice.